The Philippine local government water sector - Lawrence G. Velasco; Charlotte Justine D. Sicat; Angel Faye Castillo; Ricxie Maddawin (Philippine Institute for Development Studies (PIDS), 2020)
In 2010, the United Nations, through Resolution No. 64/292, recognized the human right to water and sanitation and its' being essential to the realization of all human rights (United Nations General Assembly 2010). In 2016, water and sanitation were promoted to a full-fledged goal as the Sustainable Development Goal No. 6, to "Ensure availability and sustainable management of water and sanitation for all." The Philippine Development Plan 2017-2022 identifies water supply and sanitation (WSS) as essential to "accelerate strategic infrastructure development" (NEDA 2017). Further highlighting this in NEDA's Philippine Water Supply and Sanitation Master Plan 2019-2030. Finally, though these priorities are global and national, the attainment of 100% access to potable water lies heavily on local government delivery of the devolved water service. Attaining these goals require identifying what kind of good water supply is and looking for the best economic framework for its provision. Water is a complex good. It could be a common resource (the water source) that, if unregulated, would have negative externalities leading to overconsumption. In addition, it could also be a natural monopoly (the process of treating and distributing water) faced with large sunk costs needing some form of regulation to avoid usurious pricing. Also, as a natural monopoly, the optimal provision of potable water might require coordination across local governments because of possible economies of scale across boundaries. This would need coordination and political will. [...]
Keywords: 330; Water district; water infrastructure; water tariff; strategic investment coordination